Translanguaging pedagogy in teaching English for Academic Purposes: Researcher-teacher collaboration as a professional development model. (August 2020) - Liu, Jiajia Eve; Lo, Yuen Yi; Lin, Angel M.Y.
Abstract: Research has shown both the potential advantages of translanguaging pedagogy in English for Academic Purposes (EAP) contexts and some challenges facing teachers. However, there is still paucity of research on how to provide professional support for teachers to develop translanguaging pedagogy. This article focuses on a design-based research (DBR) study in which a teacher collaborated with a researcher in an EAP course at a university in China to co-develop teacher capacity in using translanguaging pedagogy. Findings from classroom observations, researcher-teacher lesson co-planning meetings, post-lesson sharing sessions and interviews have shown changes in the teacher's beliefs and practices of using translanguaging pedagogy and several challenges she encountered, particularly the conflicts between the monolingual ideology in traditional TESOL discourses and the recent translanguaging pedagogical principles. This article suggests that researcher-teacher collaboration can be an effective strategy in helping in-service EAP teachers to reflect on and change their beliefs and practices while the process could be discursive. It calls for further explorations with teachers on principles that value multilingual speakers' full linguistic and semiotic repertoires in teaching and learning EAP and investigations of how these principles can be realized for emerging EAP programs in universities in China and other similar contexts.